2013
DOI: 10.1039/c3nr02822d
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide: firm support for catalytically active palladium nanoparticles and game changer in selective hydrogenation reactions

Abstract: Simultaneous decomposition and reduction of a Pd(2+) complex in the presence of graphene oxide (GO) lead to the formation of Pd(0)-nanoparticles (Pd-NPs) with average sizes of 4 nm firmly anchored on reduced graphene oxide (RGO) sheets. The Pd-NP/RGO hybrids exhibited remarkable catalytic activity and selectivity in mild hydrogenation reactions where the acidic properties of RGO play an active role and may act as an important game-changer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…16,[20][21][22][23][24] Some studies have also reported that palladium nanoparticles supported on CNT or rGO had high catalytic activity for hydrogenation reactions. [25][26][27][28] In this work, we synthesized a 3D porous rGO-CNT hydrogel by the hydrothermal treatment of an aqueous dispersion of graphene oxide (GO) and CNTs and subsequently synthesized a Pd/rGO-CNT nanocomposite catalyst by the wet impregnation method for hydro-purification of CTA. The performance of the catalyst was compared with those of Pd/rGO, Pd/functionalized multiwalled CNTs (Pd/FMWCNTs), and a commercial activated carbon supported Pd catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…16,[20][21][22][23][24] Some studies have also reported that palladium nanoparticles supported on CNT or rGO had high catalytic activity for hydrogenation reactions. [25][26][27][28] In this work, we synthesized a 3D porous rGO-CNT hydrogel by the hydrothermal treatment of an aqueous dispersion of graphene oxide (GO) and CNTs and subsequently synthesized a Pd/rGO-CNT nanocomposite catalyst by the wet impregnation method for hydro-purification of CTA. The performance of the catalyst was compared with those of Pd/rGO, Pd/functionalized multiwalled CNTs (Pd/FMWCNTs), and a commercial activated carbon supported Pd catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The most famous method, the mechanical exfoliation of graphite based on the adhesive tape use [28,43], leads to production of high-quality and high-mobility graphene flakes, but this method is cumbersome, extremely low in yield and it is consequently more difficult to scale-up [44]. Several alternative strategies have been developed since then to achieve scalable production of graphene sheets, including metal ion intercalation [29], liquid phase exfoliation of graphite in organic solvents [24,45,46], chemical vapor deposition (CVD) on transition metal catalysts (Ni, Cu, ZnS, Fe) [25][26][27]44], vacuum graphitization of silicon carbide (SiC) [47,48], bottom up organic synthesis of large polycyclic aromatic hydrocarbons (PAHs) [32,33,49], and chemical exfoliation/reduction from graphite oxide (GO) [50,51], resulting in the formation of reduced graphene oxide (rGO). This last approach is considered one of the most promising routes for the large-scale production of graphene, mainly due to its solution-processability and change of properties achieved via inclusion of functional groups during the oxidation/reduction processes.…”
Section: Scope Of the Assessmentmentioning
confidence: 99%
“…86 In another work, graphene-supported Pt NPs of 2-3 nm in diameter were prepared by exploiting the nucleation of H 2 PtCl 6 on GO surfaces, which showed remarkable catalytic Please do not adjust margins Please do not adjust margins performance in the reduction of various alkenes and alkynes to the corresponding alkanes with yields exceeding 99%. Recently, Maser and coworkers reported a simultaneous decomposition-reduction approach for the synthesis of rGOsupported Pd NPs that displayed a good efficiency for the hydrogenation of a variety of olefinic substrates including acetophenone, cyclohexene, and 1,3,5-cycloheptatriene.…”
Section: Hydrogenation Of the C=c Bondmentioning
confidence: 99%